Statins and risk of breast cancer recurrence - Sakellakis M; Akinosoglou K; Kostaki A; Spyropoulou D; Koutras A (Breast Cancer: Targets and Therapy, 2016)
Minas Sakellakis,1 Karolina Akinosoglou,1 Anastasia Kostaki,2 Despina Spyropoulou,1 Angelos Koutras,1 1Department of Medicine, Division of Oncology, University Hospital, Patras Medical School, Patras, 2Department of Statistics, Athens University of Economics and Business, Athens, Greece Background: The primary end point of our study was to test whether the concurrent use of a statin is related to a lower risk of recurrence and increased relapse-free survival in patients with early breast cancer. Materials and methods: We reviewed 610 female patients with stage I, II, or III breast cancer who had been surgically treated and who had subsequently received at least adjuvant chemotherapy in order to prevent recurrence. Results: Among the 610 patients with breast cancer, 83 (13.6%) were receiving a statin on a chronic basis for other medical purposes. Overall, statin users displayed longer mean relapse-free survival (16.6 vs 10.2 years, P=0.028). After data had been adjusted for patient and disease characteristics, statin users maintained a lower risk of recurrence. This favorable outcome in statin users was particularly evident when we included only younger patients in the analysis (20 vs 10 years, P=0.006). Conclusion: Statins may be linked to a favorable outcome in early breast cancer patients, especially in younger age-groups. Keywords: statins, breast, cancer, adjuvant, recurrence